Parent Joint AB Blood Group Is Associated With Clinical Outcomes of in vitro Fertilization and Intracytoplasmic Sperm Injection Treatment in Chinese Women - Bao, Xiao; Zhao, Feifei; Shi, Hao; Bu, Zhiqin; Liang, Yuling; Sun, Yingpu (Frontiers in Medicine, 2022)
Background A number of publications have examined the relation between blood group and female infertility including ovarian reserve, recurrent miscarriage, and live birth. However, there is a lack of literature investigating joint mother/father ABO blood type in a large cohort. This study aimed to investigate the association between couple combinations for ABO blood groups and assisted reproductive technology (ART) outcomes in patients undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI). Methods This retrospective cohort study included 30,717 couples who underwent IVF cycles between 2010 and 2019. The clinical outcomes of IVF treatment were the primary outcome. History of spontaneous miscarriage, embryo quality, and birth sex, weights, defects rate were also studied. Results There was no difference in the baseline demographics between the blood type groups. There was a statistically significant positive association between the combination of female blood type AB and male blood type AB with biochemical pregnancy, clinical pregnancy, and live birth rate (OR 1.36; 95% CI, 1.05–1.78; P = 0.02 and OR 1.31; 95% CI, 1.0–1.68; P = 0.031 and OR 1.28; 95% CI, 1.01–1.63; P = 0.041 respectively). No statistically significant difference was observed between joint mother/father ABO blood types and high-quality embryo rate, early abortion rate, birth sex, birth weights, and birth defect rate. Conclusions Our findings suggest that the success rate of IVF/ICSI cycles in parent mating AB blood type is higher than that in other blood type combination groups.